BIOACCUMULATION OF HEAVY METAL IN SOIL AND DIFFERENT PLANT PARTS OF ALBIZIA PROCERA (ROXB.) SEEDLING - PREETI PANDEY; A. K. TRIPATHI (The Bioscan, 2010)
An investigation was conducted to study the differential action of heavy metals such as Cd, As and Pb on Albizia procera. The study of bioaccumulation of heavy metals such as Cd, As and Pb in soil, root, shoot and leafs of Albizia procera. Plants were supplemented with 1mg/L, 5mg/L and 10mg/L concentration of heavy metals per week for a period of four months. The accumulation study showed increase of all metals when the exposure time and concentration were increased. In 10mg/L concentration samples, leaf had higher Cd and As contents than root suggesting that the metal were bound to the leave cells, while in Pb treatment soil had higher content of Pb than leaves, for all concentration, suggesting that metal were bound to the root cells and were partially transported to the leaves.